The Improvement of Teaching Ideological and Political Theory Courses in Universities Based on Immersive Media Technology - Su, Li; Li, Mengzuo (Frontiers in Psychology, 2022)
This paper focuses on the characteristics of immersive media technology and the advantages, problems and solutions in applying this technology to improve the teaching effectiveness of ideological and political theory courses in colleges and universities. Firstly, it introduces the current development and characteristics of immersive media technology. Secondly, it analyzed the outstanding advantages of immersive media technology in teaching from the following perspectives: virtual reality and augmented reality; sensory stimulation and emotional experience; and human-computer interaction and self-harmony. Thirdly, it puts forward the ways to improve the teaching effectiveness based on immersive media technology from the aspects of theoretical study, history study and practical study of ideological and political theory courses in colleges and universities. Finally, it discusses the problems in applying immersive media technology to teaching the above courses and puts forward some solutions.